PEMODELAN ARSITEKTUR ENTERPRISE PERGURUAN TINGGI - Agung Wahana (STMIK Mardira Indonesia, Bandung, 2015)
Enterprise Architecture Planning (EAP) as a method for building information architecture. EAP is a planning method oriented architecture business requirements consist of data architecture, application and technology as well as planning the implementation of the architecture that has been created to support the business activities for the achievement of the organization's mission. EAP describes the architecture of the data, applications and technologies required to support the organization's business. Many developments of Information Technology (IT) failed due to the development of IT needs are based on the current needs without any planning. Higher Education as a provider of higher education need to plan the enterprise architecture. Enterprise architecture that is modeled on the universities, include: data architecture, application architecture, and technology Architecture. Keywords: Information Technology, Enterprise Architecture Planning, Data Architecture, architectural design Applications, Architecture Technology Abstrak Enterprise Architecture Planning (EAP) sebagai salah satu metode untuk membangun sebuah arsitektur informasi. EAP adalah suatu metode perencanaan arsitektur yang berorientasi pada kebutuhan bisnis yang terdiri dari arsitektur data, aplikasi dan teknologi serta rencanaan implementasi dari arsitektur yang telah dibuat untuk mendukung aktivitas bisnis demi pencapaian misi organisasi. EAP menjelaskan arsitektur data, aplikasi dan teknologi yang dibutuhkan untuk mendukung bisnis organisasi. Banyak pengembangan Information Technology (IT) mengalami kegagalan karena pengembangan kebutuhan IT dibuat berdasarkan kebutuhan saat itu tanpa ada perencanaan. Perguruan Tinggi sebagai penyelenggara pendidikan tinggi perlu merencanakan arsitektur enterprise. Arsitektur enterprise yang dimodelkan pada perguruan tinggi, meliputi: arsitektur data, arsitektur aplikasi, dan arsitektur teknologi. Kata Kunci: Information Technology, Enterprise Architecture Planning, Arsitektur Data, Arsiterktur Aplikasi, Arsitektur Teknologi